Moisture-dependent physical properties of barley grains - Tavakoli, Mahmoud; Tavakoli, Hamed; Rajabipour, Ali; Ahmadi, Hojat; Gharib-Zahedi, Seyed Mohammad Taghi (International Journal of Agricultural and Biological Engineering, 2010)
<!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> Designing equipment for processing, sorting, sizing and other post-harvest operations of agricultural products requires information about their physical properties. This study was carried out to evaluate the effect of moisture content on some physical properties of barley grains. Four levels of moisture content ranging from 7.34% to 21.58% (d.b.) were used. The average length, width, thickness, arithmetic mean diameter, geometric mean diameter, thousand grain mass, sphericity, surface area and repose angle increased from 8.91 to 9.64 mm, 3.30 to 3.74 mm, 2.58 to 2.98 mm, 4.93 to 5.45 mm, 4.23 to 4.75 mm, 44.48 to 51.30 g, 47.55% to 49.35%, 56.66 to 71.09 mm2 and 31.16° to 36.90°, respectively, as moisture content increased from 7.34% to 21.58% (d.b.). The bulk density, true density and porosity were found to decrease with increasing moisture content. The static friction coefficient of the grains increased linearly against various surfaces (plywood, glass and galvanized iron sheet) as the moisture content increased. At all moisture content, the maximum friction was offered by plywood, followed by galvanized iron sheet and glass surface. Keywords: barley, moisture content, angle of repose, coefficient of friction DOI: 10.3965/j.issn.1934-6344.2009.04.084-091 Citation: Mahmoud Tavakoli, Hamed Tavakoli, Ali Rajabipour, Hojat Ahmadi, Seyed Mohammad Taghi Gharib-Zahedi. Moisture-dependent physical properties of barley grains. Int J Agric & Biol Eng, 2009; 2(4): 84<span style="line-height: 140%; font-family: